Impact of Non-Renewable Energy Consumption and Economic Growth on Carbon Emission in Nigeria - Dansofo, Adama T.; Saheed, Zakaree S.; Alexander, Anfofum A.; Muktar, Mustapha; Sahad, Suleiman; Alfa, Yakubu; Dampome, Moses; Ibubor, Jude O.; Samuel, Gambo J.; Ojo, Sanya (ABUAD Journal of Social and Management Sciences, 2024)
The study examines the impact of non-renewable energy consumption and economic growth on carbon emission using an annual data spanning from 1980 to 2022. The Autoregressive Distributed Lag Model was employed. From the analysis, the co-integration results reveal that there is a long-run relationship between the variables under study. Furthermore, both the long-run and short-run Autoregressive Distributed Lag (ARDL) estimates unequivocally demonstrate that both economic growth and the non-renewable energy consumption exert statistically significant, and positive impacts on CO2 emissions. In essence, they jointly contribute to the observed increase in CO2 emissions over the study period. Based on the findings, it is recommended that adequate regulations, restrictions and innovative ways in fostering economic growth through energy consumption from non-renewable energy sources are implemented alongside policies from energy regulatory Commission and environmental protection agencies, to explore avenues to invest in, and promote, carbon-reducing technology in production processes to mitigate against the effects and degradation of the environment.